2013
DOI: 10.1371/journal.ppat.1003441
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Double-negative T Cells in Sooty Mangabeys Mediate T-helper Functions Irrespective of SIV Infection

Abstract: Studying SIV infection of natural host monkey species, such as sooty mangabeys, has provided insights into the immune changes associated with these nonprogressive infections. Mangabeys maintain immune health despite high viremia or the dramatic CD4 T cell depletion that can occur following multitropic SIV infection. Here we evaluate double-negative (DN)(CD3+CD4−CD8−) T cells that are resistant to SIV infection due to a lack of CD4 surface expression, for their potential to fulfill a role as helper T cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 75 publications
(107 reference statements)
4
29
0
Order By: Relevance
“…DN T-cells are associated with reduced immune activation and high levels of immune-suppressive cytokines, including TGF-b and IL-10, in HIV infection (Petitjean et al, 2012). In simian immunodeficiency virus (SIV) infection of non-human primates, DN T-cells are capable of performing CD4 + T-cell-like helper functions whilst remaining refractory to SIV infection and are associated with a lack of clinical disease progression (Milush et al, 2011;Sundaravaradan et al, 2012Sundaravaradan et al, , 2013. Thus, the increased numbers of DN T-cells in HPgV infection may play important roles in reducing immune activation and maintenance of immune homeostasis, contributing to improved survival in HIV co-infection.…”
Section: Hpgv Infects Diverse Haematopoietic Cell Types In Vitromentioning
confidence: 99%
“…DN T-cells are associated with reduced immune activation and high levels of immune-suppressive cytokines, including TGF-b and IL-10, in HIV infection (Petitjean et al, 2012). In simian immunodeficiency virus (SIV) infection of non-human primates, DN T-cells are capable of performing CD4 + T-cell-like helper functions whilst remaining refractory to SIV infection and are associated with a lack of clinical disease progression (Milush et al, 2011;Sundaravaradan et al, 2012Sundaravaradan et al, , 2013. Thus, the increased numbers of DN T-cells in HPgV infection may play important roles in reducing immune activation and maintenance of immune homeostasis, contributing to improved survival in HIV co-infection.…”
Section: Hpgv Infects Diverse Haematopoietic Cell Types In Vitromentioning
confidence: 99%
“…In sooty mangabeys, double-negative T cells, which express neither CD4 nor CD8, are thought to be responsible for the lack of disease progression in a subset of animals that undergo severe CD4 ϩ T cell depletion (11)(12)(13). Furthermore, there is evidence that CD4 downregulation and the large population of CD8␣␣ T cells observed in Patas monkeys led to the extinction of a Patas-specific SIV (14).…”
mentioning
confidence: 99%
“…Additionally, Mou et al have shown that major histocompatibility complex (MHC) class II-restricted DN T cells contribute to optimal immunity against Leishmania major in mice (23). For simian immunodeficiency virus (SIV) infections, Sundaravaradan and colleagues reported that multifunctional DN T cells mediated a T helper cell function during SIV infection of mangabeys; these animals remained healthy despite high viremia and CD4 ϩ T cell depletion (24). While the role of DN T cells in protecting humans against microbial pathogens is less clear, DN T cell populations have been shown to expand during staphylococcal and mycobacterial infections (21,25).…”
Section: Discussionmentioning
confidence: 99%